BAHASA DAN SASTRA ARAB MASA BANI ABBASIYAH DAN IMPLIKASINYA TERHADAP BAHASA DAN SASTRA ARAB KONTEMPORER - Amiruddin; Lenni Suriyanti; Andi Abdul Hamzah; Kamaluddin Abunawas (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2025)
This research discusses the existence of the Arabic language during the Abbasid Era, known as the golden period of development of Arabic language and literature, marked by unprecedented intellectual, institutional and cultural progress. This research aims to analyze the dynamics of the development of Arabic language and literature in the Abbasid era by highlighting the factors that encouraged this progress—such as large-scale translations, cultural interactions across civilizations, scientific patronage, and the maturation of literary criticism—and examining their implications for the development of contemporary Arabic language and literature. This study shows that the Abbasid period formed a solid foundation for linguistic traditions through the codification of grammar, enrichment of vocabulary, and the influence of rationalist thought which encouraged literary creativity. In contemporary times, this legacy is reflected in the renewal (tajdīd) of modern Arabic literature, the formation of new critical theories, and the revitalization of the Arabic language through standardization movements and the development of terms. The results of this study confirm that the historical continuity between the Abbasid period and the modern era plays an important role in maintaining the relevance of Arabic language and literature as a medium for intellectual expression, aesthetics and cultural identity in the current global context. Penelitian ini membahas eksistensi bahasa Arab pada Masa Bani Abbasiyah dikenal sebagai periode keemasan perkembangan bahasa dan sastra Arab, ditandai oleh kemajuan intelektual, institusional, dan kultural yang belum pernah terjadi sebelumnya. Penelitian ini bertujuan untuk menganalisis dinamika perkembangan bahasa dan sastra Arab pada era Abbasiyah dengan menyoroti faktor-faktor yang mendorong kemajuan tersebut—seperti penerjemahan besar-besaran, interaksi budaya lintas peradaban, patronase ilmiah, dan pematangan kritik sastra—serta menelaah implikasinya terhadap perkembangan bahasa dan sastra Arab kontemporer. Studi ini menunjukkan bahwa periode Abbasiyah membentuk fondasi kokoh bagi tradisi kebahasaan melalui kodifikasi gramatika, pengayaan kosakata, serta pengaruh pemikiran rasionalis yang mendorong kreativitas sastra. Di masa kontemporer, warisan tersebut tercermin dalam pembaruan (tajdīd) sastra Arab modern, pembentukan teori kritik baru, serta revitalisasi bahasa Arab melalui gerakan standardisasi dan pengembangan istilah. Hasil kajian ini menegaskan bahwa kesinambungan historis antara periode Abbasiyah dan era modern berperan penting dalam mempertahankan relevansi bahasa dan sastra Arab sebagai medium ekspresi intelektual, estetika, dan identitas budaya dalam konteks global saat ini.